Genetic Variants in Genes Regulating Lens Capsule Structure and Stability in Dead Bag Syndrome – Part 1 - Vasavada, Abhay R; Rajkumar, Sankaranarayanan; Vasavada, Shail A; Vasavada, Vaishali; Dholu, Suchi; Meena, Vijaylaxmi (Journal of cataract and refractive surgery, 2025)
To investigate potential genetic variants associated with spontaneous Posterior Capsule Rupture (sPCR) in patients diagnosed with Dead Bag Syndrome (DBS). Iladevi Cataract and Intraocular Lens (IOL) Research Centre and Raghudeep Eye Hospital, Ahmedabad, Gujarat, India. Laboratory Study. We collected blood samples from 30 DBS patients and 37 controls. Whole-exome sequencing (WES) was performed. Genetic variants in genes encoding extracellular matrix (ECM) components of the lens capsule were screened. The association of selected variants with DBS was analysed using the Optimal Unified Sequence Kernel Association Test (SKAT-O) in R and Logistic Regression. Genes showing significant associations were further analysed using in silico predictions via the Ensembl Variant Effect Predictor (eVEP) to assess their potential impact on protein function. Three genes-FBN2 (P=.027, OR=4.9, 95% CI=0.56-42.72), LAMB1 (P=.005, OR=11.0, 95% CI=1.56-77.31), and LAMB2 (P=.091, OR=8.2, 95% CI=1.03-65.57)-were found to be positively associated with DBS. A total of 15 distinct, functionally deleterious genetic variants, including 6 in FBN2, 3 in LAMB1, and 6 in LAMB2 genes were identified across 17 (56.7%) patients with DBS. Of the 17 patients, 5 (29.4%) carried a common genetic variant (p.Ile1547Thr; rs35915664, MAF=0.016) in the LAMB1 gene, which was absent in controls. The genetic variants found in FBN2, LAMB1, and LAMB2 genes may compromise the strength and stability of the lens capsule over time, predisposing individuals to DBS and sPCR later in life. The study shows for the first time that the DBS has a genetic predisposition.